2016
DOI: 10.21451/1984-3143-ar736
|View full text |Cite
|
Sign up to set email alerts
|

The effects of propolis on sperm quality, reproductive organs and testicular antioxidant status of male rats treated with cyclosporine-A

Abstract: This study was designed to determine the effects of propolis on the quality of sperm and reproductive organs in male rats treated with cyclosporine-A. In this study, 24 male Sprague-Dawley rats (280-300 g BW) at 8-10 weeks of age were used. The rats were randomly divided into control and 3 treatment groups. Each rat was placed into a cage. During 21 days (experimental period), Group 1 served as control group; Group 2 (CsA) was given 15 mg/kg BW/day of CsA by subcutaneously; Group 3 (P) was given 100 mg/kg BW/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
3
16
0
Order By: Relevance
“…The levels of Cu in seminal plasma and serum of fertile male rats were significantly lower than those in subfertile male rats (Aydemir et al, ; Eidi et al, ). Similar to our findings, it was reported that propolis had significantly ameliorative effects on sperm motility and concentration, seminal vesicles, prostate and right cauda weights ( p < .01), abnormal sperm rate, right and left epididymis weights ( p < .05) in Sprague Dawley rats treated with cyclosporine‐A (Gul Baykalir et al, ). Also, Sakhaee et al () reported that a significant decrease in sperm motility, concentration and viability as the adverse effects of Cu on male Wistar albino rat fertility.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The levels of Cu in seminal plasma and serum of fertile male rats were significantly lower than those in subfertile male rats (Aydemir et al, ; Eidi et al, ). Similar to our findings, it was reported that propolis had significantly ameliorative effects on sperm motility and concentration, seminal vesicles, prostate and right cauda weights ( p < .01), abnormal sperm rate, right and left epididymis weights ( p < .05) in Sprague Dawley rats treated with cyclosporine‐A (Gul Baykalir et al, ). Also, Sakhaee et al () reported that a significant decrease in sperm motility, concentration and viability as the adverse effects of Cu on male Wistar albino rat fertility.…”
Section: Discussionsupporting
confidence: 91%
“…This particular effect (as the first mechanism) may associate with scavenging by propolis of the free radicals. The second mechanism could be the ability prevent of propolis to the activity of xanthine oxidase (XAO), which is generated by free radicals (Attia et al, 2012;Gul Baykalir et al, 2016). It has been reported that the various phenolic and flavonoid components of propolis can able to be capable of scavenging by remove or deactivate free radicals and so, preventing the oxidised of lipids and the breakdown of some compounds such as vitamin C during oxidative stress (Attia et al, 2012;Kumar, Ahmad, Dang, & Husain, 2008;Frozza et al, 2013;Tatli Seven et al, 2009) The Cu causes to alterations in levels of LH and testosterone hormones (Chang, Choi, Kim, & Park, 2011), reduction the activity of 17-beta-hydroxysteroid dehydrogenase enzyme and damage to histoarchitecture of testicular tissues (Khushboo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, immune suppression must be used for the long term, leading to a series of side effects and increased risks of cardiovascular disease and cancer. Blood CsA concentrations are inversely related to sperm density and concentration in the semen of male patients after renal transplantation, leading to reproductive disorders (Baykalir, Seven, & Gur, ). Animal experimental results have indicated that CsA had reproductive toxicity, interfering with spermatogenesis and leading to male reproductive dysfunction and male sterility (Baykalir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood CsA concentrations are inversely related to sperm density and concentration in the semen of male patients after renal transplantation, leading to reproductive disorders (Baykalir, Seven, & Gur, ). Animal experimental results have indicated that CsA had reproductive toxicity, interfering with spermatogenesis and leading to male reproductive dysfunction and male sterility (Baykalir et al, ). The effects of different immunosuppressive regimens in the therapeutic dose range on the testicular development, semen quality, sex hormone levels and testicular tissue damage were explored in UN rats.…”
Section: Discussionmentioning
confidence: 99%